Pengaruh Pengembangan Karir terhadap Motivasi dan Dampaknya terhadap Kinerja Karyawan (Studi Kasus di PT. Barata Indonesia (Persero) Gresik) - ANNISA PUTRI, WINDA; FRIANTO, AGUS (Jurnal Ilmu Manajemen (JIM), 2019)
Abstract PT Barata Indonesia (Persero) is a state-owned company (State-owned enterprises) engaged in the construction and manufacturing. The company has a clear organizational goals to be able to compete in the competition of the industry. Performed career development PT Barata Indonesia (Persero) can be either rising Office conducted anytime and rising levels in his post or be called SLI conducted at least once a year. In motivating employees the company compensate called Komkar (compensation for Work) and Inkar (Work Incentives) to improve the performance of employees. The purpose of this research is to find out and analyze the influence of career development towards motivation and its impact on the performance of employees at PT Barata Indonesia Gresik (Persero). This research is a type of quantitative research with the total sample as much as 193 employees remain. Measuring instrument used were, interview, observation, and questionnaire. Analysis of the statistic used is the Structural Equation Modeling (SEM) with the help of software Analysis of Moment Structures (AMOS). The results of this study explain that career developments has no effect on employee performance, while motivation has a significantly positive effect on employee performance and career development has a significant positive effect on motivation. Keywords: Career development; Employee performance; Motivation.